Early pregnancy plasma fatty acid profiles of women later diagnosed with gestational diabetes - Rikard Landberg; Ingibjorg Gunnarsdottir; Thorhallur Ingi Halldorsson; Bryndis Eva Birgisdottir; Ellen Alma Tryggvadottir; Laufey Hrolfsdottir; Ingibjorg Th Hreidarsdottir; Hildur Hardardottir (BMJ Open Diabetes Research & Care)
Introduction Fatty acid (FA) concentrations have previously been associated with gestational diabetes mellitus (GDM). However, few studies on GDM have examined FA profiles in early pregnancy or before diagnosis. This study aimed to compare early pregnancy plasma FA profiles of women with and without GDM diagnoses as well as their reported dietary consumption.Research design and methods The subjects comprised 853 women from the prospective study: Pregnant Women in Iceland II (PREWICE II), attending their 11–14 weeks ultrasound appointment in 2017–2018. During the visit, blood samples were collected for plasma FA analysis, and dietary habits were assessed using a short food frequency questionnaire. Information on GDM diagnoses was then later extracted from medical records. Differences in FA profile between GDM cases and non-cases were evaluated using the Mann-Whitney U test.Results GDM was diagnosed in 127 women (14.9%). Concentrations of saturated fatty acids, monounsaturated fatty acids, polyunsaturated fatty acids (PUFA) n-6, PUFA n-3 and total FA were higher in the women who later developed GDM compared with those who did not (p≤0.05). The medians for total FA were 2898 μg/mL for the women with GDM and 2681 μg/mL for those without GDM. Mean adjusted difference for total FA between the groups was 133 μg/mL (95% CI 33 to 233). Similar results were observed in prepregnancy normal-weight women and overweight women/women with obesity. Overall diet quality in early pregnancy appeared to be lower among the women later diagnosed with GDM.Conclusion We found that plasma FA profiles in early pregnancy were different for women later diagnosed with GDM compared with those who were not, independent of the women’s body mass index.